THE APPLICATION OF HYBRID CONTRACT SYSTEM IN GALA BANK FINANCING ACCORDING TO FIQH MUAMALAH: A STUDY ON KSPPS BAITUL QIRADH ABDYA, INDONESIA - Yusran Hadi, Muhammad; Utari Silvia Roja (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2025)
Bank Gala is a product of KSPPS Baitul Qiradh Gala in Abdya district of Aceh, which supports local farmers by offering profit-sharing loans through two contract financing systems. This study addresses the legality of the two-contract system implementation in the financing scheme. The study uses a qualitative method, with primary and secondary data from interviews, observations, and documentation. The results show that, first, provisions and practices for implementing the two-contract system in sharia financing at KSPPS Baitul Qiradh Gala Muamalah are based on the company's provisions and the fatwa. Second, the Acehnese Ulama argue that the two-contract system's application to sharia financial institutions is the same as the Indonesian ulama's opinion: the system is permissible as long as the two contracts complement or perfect each other, which is Islamic. Third, the Islamic economic law perspective on implementing the two contracts for Bank Gala financing at KSPPS is based on its provisions, with the benefit of combining the two contracts, there is a principle of risk sharing between the customer and the cooperative, mutual help, and investment can benefit both parties by sharing profits and other benefits.